2013
DOI: 10.3109/19401736.2013.772152
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the clamMactra veneriformis(Bivalvia: Mactridae): Has a unique non-coding region, missingatp8and typicaltRNASer

Abstract: Mactra veneriformis (Bivalvia: Mactridae) is one commonly cultured bivalve species in the western Pacific Ocean. In the current study, the complete mitrochondrial DNA (mtDNA) of the clam M. veneriformis was determined. The M. veneriformis mt genome is 16,854 bp in length and encodes 34 genes on the same strand, including 12 protein-coding genes (PCGs), 2 ribosomal RNA genes and 20 transfer RNA genes. The length of 12 PCGs is 11,358 bp, which accounts for 67.4% in whole mt genome. The proportion is similar to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The control region (CR) is the largest non-coding region; it usually presents a high AT content and is therefore also known as the A + T rich region 29 . It is an essential element involved in mitochondrial genome replication and transcription initiation 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control region (CR) is the largest non-coding region; it usually presents a high AT content and is therefore also known as the A + T rich region 29 . It is an essential element involved in mitochondrial genome replication and transcription initiation 30 .…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, there are significant differences in the intergenic spacers and overlapping nucleotides of the two species, and these species of limpets also present large variations compared with other families (e.g., Nacellidae, Acmaeidae and Patellidae) [24][25][26][27][28] . The control region (CR) is the largest non-coding region; it usually presents a high AT content and is therefore also known as the A + T rich region 29 . It is an essential element involved in mitochondrial genome replication and transcription initiation 30 .…”
mentioning
confidence: 99%
“…Mactridae includes 348 recognized species distributed in the world, but only two mitochondrial genomes (M. veneriformis and Coelomactra antiquata) have been reported recently (Meng et al, 2013a;Meng et al, 2012;Meng et al, 2013c). Mitochondrial genome of the commercially important M. chinensis has not been reported.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition to the mitochondrial genome sequence of M. chinensis from this study, the three recent reported mitochondrial genomes from Mactra veneriformis and Coelomactra antiquata (two genomes from the latter with specimens from Ri Zhao, Shandong Province in northern China and Zhang Zhou, Fujian Province in southern China) (Meng et al, 2013a;Meng et al, 2012;Meng et al, 2013c) were included in the phylogenetic analysis which includes a total of 25 bivalve mitochondrial genomes.…”
Section: Genetic Distance and Phylogenetic Analysis Within Bivalviamentioning
confidence: 99%
“…One possible way to control for the effects of mitochondrial variants in genome-wide association study is to type diagnostic mitochondrial polymorphisms to allow for the mitochondrial haplogroup membership to be inferred and used as a covariate. 42 …”
Section: Confounding By Cytonuclear Ldmentioning
confidence: 99%